Peran Surat Berharga Syariah Negara (SBSN) Dalam Pertumbuhan Ekonomi Indonesia - Zain, Rahma Sari; Winarsih, Safitri; Situmorang, Nurul Utami (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
Given that it has the highest economic growth rate and highest concentration of Muslims anywhere in the world, Indonesia is an ideal location for the development of the Islamic economy. The primary source of funding is the issuance of Sukuk, or Sharia Securities. Due to the availability of sukuk, the government is better able to finance its budget deficit. The cost of debt can be decreased by the government. This study's objectives are to ascertain 1) how sukuk have evolved in Indonesia and 2) how sukuk have contributed to the economic development of the nation. Both qualitative research techniques and literary analysis tools are used in this study. Secondary data is information that was used in this study and comes from previously published articles or other works. The following are the study's findings: 1) Indonesia's government has made retail sukuk (SR) accessible, particularly SR 001-SR 013. According to the APBN's plans, the country issues a growing number of sukuk from one year to the next. 2) The role that the state sukuk plays is very advantageous, including financing project development, promoting the expansion of Islamic financial markets, setting up branches there, developing new investment instruments, and using public funds.